Ethnobotanical survey and conservation assessment of medicinal plants in pannagam, jaffna, sri lanka - Karunya, S.; Saruja, N.; Sivagajendran, S.; Sathiyaseelan, V. (University of Colombo, 2025)
Siddha medicine emphasizes the therapeutic use of medicinal plants as a primary approach to managing various illnesses and promoting holistic wellness. This study aimed to document and analyze the diversity of medicinal plant species in the Pannagam region of Jaffna, Sri Lanka, to support conservation efforts. Fieldwork was conducted from March 2024 to March 2025 using the Belt Transect Method to identify and record plant species. Specimens were collected and verified with the Herbarium at the Faculty of Siddha Medicine, University of Jaffna. A total of 177 medicinal plant species belonging to 55 botanical families were identified, with the Fabaceae family being the most represented. Life cycle analysis showed that 21.47% of species were annuals, 8.47% biennials, and 70.06% perennials. Morphological classification revealed 34.46% were shrubs, followed by trees (24.85%), herbs (20.92%), climbers (16.95%), and cacti (2.82%). The most commonly used plant parts for medicinal purposes were leaves (n = 76), roots (n = 69), and seeds (n = 34), with other parts like bark, flowers, whole plant, and stem also utilized. Despite the abundance of medicinal plants, their habitats are under increasing threat from urban development, herbicide use, and limited public knowledge of their value. The findings highlight Pannagam's rich ethnobotanical resources and the urgent need for effective conservation strategies. These should include habitat protection, sustainable harvesting, and awareness programs to ensure the long-term preservation of these vital plant resources.
Keywords: Medicinal plants; Pannagam; Conservation